Diagnosis and treatment of obstructive sleep apnea - Myśliwiec, Natalia; Pniak, Michał; Miklis, Paweł; Mawlichanów, Maciej; Ciesielska, Aleksandra; Sieradzka, Aleksandra; Szerej, Krzysztof; Kot, Alicja; Wojtczak, Marta; Różycki, Adrian (Quality in Sport, 2025)
Obstructive sleep apnoea (OSA) is a prevalent disorder characterized by repeated episodes of partial or complete upper airway collapse during sleep, resulting in intermittent hypoxia, hypercapnia, and sleep fragmentation. Common in middle-aged and older adults, its pathogenesis is multifactorial, encompassing obesity, craniofacial abnormalities, altered upper airway muscle function, pharyngeal neuropathy, and fluid redistribution to the neck. These episodes trigger sympathetic activation, oxidative stress, and systemic inflammation, contributing to daytime sleepiness, road traffic accidents, and a spectrum of cardiovascular and metabolic comorbidities such as hypertension, arrhythmias, coronary artery disease, stroke, and diabetes mellitus. The efficacy of therapy in reversing chronic sequelae remains uncertain. Continuous positive airway pressure (CPAP) is the first-line treatment in severe cases, although patient adherence varies between 60–70%. Alternative modalities, including bi-level positive airway pressure, adaptive servo-ventilation, oral appliances, and surgical interventions, may be employed. Weight reduction and combined treatment strategies hold promise but require validation in well-designed randomized controlled trials.